2015
DOI: 10.1007/s40256-015-0125-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Targets of Drug Treatment for Pulmonary Hypertension

Abstract: Biomedical advances over the last decade have identified the central role of proliferative pulmonary arterial smooth muscle cells (PASMCs) in the development of pulmonary hypertension (PH). Furthermore, promoters of proliferation and apoptosis resistance in PASMCs and endothelial cells, such as aberrant signal pathways involving growth factors, G protein-coupled receptors, kinases, and microRNAs, have also been described. As a result of these discoveries, PH is currently divided into subgroups based on the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 143 publications
(154 reference statements)
0
31
0
Order By: Relevance
“…1 This beneficial effect on cell survival has been exploited clinically as a host of potent KEAP1-reactive electrophiles have been tested or approved for the treatment of various diseases including multiple sclerosis (dimethyl fumarate), cancer prevention (Oltipraz), and pulmonary arterial hypertension (Bardoxolone methyl), among others. [2][3][4] Despite these beneficial effects, a wealth of new evidence has suggested that many human cancers, including those of the lung, breast, colon, ovaries, and pancreas, have mutations which promote the stability and activity of NRF2. 5,6 A number of mechanisms that lead to constitutive NRF2 activity in cancer have been demonstrated, including mutations in KEAP1 and NRF2, mutations in fumarate hydratase leading to KEAP1 succination, KEAP1 promoter hypermethylation, and the expression of oncogenes leading to increased NRF2 transcription.…”
mentioning
confidence: 99%
“…1 This beneficial effect on cell survival has been exploited clinically as a host of potent KEAP1-reactive electrophiles have been tested or approved for the treatment of various diseases including multiple sclerosis (dimethyl fumarate), cancer prevention (Oltipraz), and pulmonary arterial hypertension (Bardoxolone methyl), among others. [2][3][4] Despite these beneficial effects, a wealth of new evidence has suggested that many human cancers, including those of the lung, breast, colon, ovaries, and pancreas, have mutations which promote the stability and activity of NRF2. 5,6 A number of mechanisms that lead to constitutive NRF2 activity in cancer have been demonstrated, including mutations in KEAP1 and NRF2, mutations in fumarate hydratase leading to KEAP1 succination, KEAP1 promoter hypermethylation, and the expression of oncogenes leading to increased NRF2 transcription.…”
mentioning
confidence: 99%
“…The loss of PAECs via BMPR2 mutations contributes to a pro-inflammatory state that would allow for immune cell infiltration, PASMC hyperproliferation, and occlusion of the vessel lumen, which is observed in PAH histology [20]. Activation of nuclear factor erythroid 2-related factor 2 (Nrf2) has been shown to improve mitochondrial function and reduce the generation of ROS and inflammation, while also reducing arterial and RV remodeling [151,152]. Currently, bardoxolone methyl, an inducer of Nrf2, is underway in a phase II clinical study in PAH patients (NCT02036970) [152].…”
Section: Novel Targets Of Emerging Metabolic Therapiesmentioning
confidence: 99%
“…These make use of the strong evidence that several varieties of circulating cells, including endothelial progenitor cells and a variety of bone marrow-derived cells, are found in the vicinity of the pulmonary vascular lesions and may play a role in disease etiology or progression (61). Closest to the clinic is use of cellbased therapies for drug delivery.…”
Section: C/fpomentioning
confidence: 99%